2013
DOI: 10.9775/kvfd.2012.8006
|View full text |Cite
|
Sign up to set email alerts
|

Peste Des Petits Ruminants (PPR) Virus Infections in Goats in the Eastern Anatolia of Turkey

Abstract: SummaryIn this study, a totally 98 materials were used consist of different samples such as blood, oro-nasal swap, lung, spleen and lymph node from goats (n=38) in the 28 flocks suspected the PPRV infection as clinically and macroscopic pathologic remarks. The goats that used in this study housed in the 11 different provinces of Eastern Anatolia. RT-PCR was used for the diagnosis of PPRV infection. PPRV nucleic acid was detected in 50 of 98 materials by RT-PCR. According to the results of RT-PCR, the PPRV nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Researchers have reported that nasal and conjunctival swab samples taken from animals with clinical symptoms are more valuable as diagnostic material. Baydar et al (2013) stated that the most valuable necropsy material for diagnostic purposes was different materials such as lymph nodes, spleen, lung, oral-nasal swab and blood, and they found that positivity rates for lymph nodes, nasal and oral swabs, blood, lung and spleen were 54.2%, 66.6%, 45%, 46.2% and 46.2% respectively. In the current study, materials such as nasal swab, lung, spleen and lymph nodes were used to diagnose PPR infection with RT-PCR.…”
Section: Ne Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have reported that nasal and conjunctival swab samples taken from animals with clinical symptoms are more valuable as diagnostic material. Baydar et al (2013) stated that the most valuable necropsy material for diagnostic purposes was different materials such as lymph nodes, spleen, lung, oral-nasal swab and blood, and they found that positivity rates for lymph nodes, nasal and oral swabs, blood, lung and spleen were 54.2%, 66.6%, 45%, 46.2% and 46.2% respectively. In the current study, materials such as nasal swab, lung, spleen and lymph nodes were used to diagnose PPR infection with RT-PCR.…”
Section: Ne Usmentioning
confidence: 99%
“…The diagnostic methods frequently used today to diagnose PPR infection are antigen-ELISA, RT-PCR and subsequent nucleotide sequencing (Forsyth and Baarrett, 1995;Balamurugan et al, 2012;Kumara et al, 2014;Saritha et al, 2015). Organ materials such as lymph nodes, spleen, liver and lung as well as oral and nasal swab samples can be used in PCR tests to identify PPRV nucleic acid (Forsyth and Baarrett, 1995;Albayrak and Alkan, 2009;Baydar et al, 2013;Sevik, 2014).…”
Section: Advances In Animal Andmentioning
confidence: 99%